CLINICAL AND PATHOLOGICAL CHANGES OF LAYING HENS (Gallus gallus domesticus) EXPERIMENTALLY POISONED BY Crotalaria spectabilis SEEDS (Leg. Papilionoideae) / Alterações clínico-patológicas de galinhas poedeiras (Gallus gallus domesticus) intoxicadas... - PEREIRA, W. A. B.; HATAYDE, M. R.; GODOY, G. S.; ALESSI, A. C.; BERCHIERI JUNIOR, A. (Ars Veterinaria, 2011)
A C. spectabilis pertence ao gênero Crotalaria, família Leguminosae e é utilizada como adubação verde. Desta forma, suas sementes podem ser colhidas juntamente com os grãos de milho e soja contaminando alimentos para animais. Para avaliar a toxicidade das sementes de C. spectabilis para galinhas poedeiras, foram utilizadas 80 galinhas "Hisex White", distribuídas nos grupos G1, G2, G3 e G4, que receberam durante 28 dias, rações contendo respectivamente: 0,00, 0,02, 0,04 e 0,06% de sementes trituradas de C. spectabilis. As aves que morreram durante o experimento, e as, sacrificadas ao final do mesmo foram necropsiadas colhendo-se fragmentos de fígado, rim, pró-ventrículo, pulmão e coração para histopatologia. Macroscopicamente verificou-se ascite, caquexia, fígado reduzido ou aumentado de volume com presença de fibrina e/ou hematomas subcapsulares. Microscopicamente, encontrou-se esteatose, congestão, hemorragia, megalocitose e necrose de hepatócitos. Assim, conclui-se que as sementes de C. spectabilis incorporadas na ração aos níveis de 0,02%, 0,04% e 0,06% são hepatotóxicas para galinhas poedeiras. Summary C. spectabilis belongs to Crotalaria genus of the Leguminosae family, and is used as "green manuring". In that manner, its seeds may be harvested along with corn and soy beans contaminating animal foods. The purpose of this work was to evaluate the toxicity of C. spectabilis seeds present in the diet fed to laying hens. Eighty "Hisex White" fowls were divided into four groups G1, G2, G3 and G4. The laying hens were fed diets containing 0.00, 0.02, 0.04 and 0.06% of crushed seeds of C. spectabilis for 28 days. Every day, fowls were monitored clinically. The fowls that died in the course of the experiment and the fowls euthanized at the end, were necropsied and fragments of liver, kidney, proventricle, lungs and heart were collected for histopathology. Macroscopic examination of poisoned fowls revealed ascites, cachexia, liver volume increased or reduced with fibrin or subcapsule hematomas. Histopathology showed steatosis, congestion, hemorrhage, megalocytosis and necrosis of hepatocytes. Therefore, the C. spectabilis seeds incorporated into diets at levels of 0.02%, 0.04% and 0.06% were hepato-toxic for laying hens.